Building on food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Food Security Pack manager with Zambia?s Programme Against Malnutrition explains how the programme is working to support small-scale farmers, and help them move from better food security towards commercial production.